Distribution of Amelanchier ovalis Medik. in the Romanian Carpathians – a critical overview - Indreica, Adrian; Puscas, Mihai; Bartok, Attila (Babes-Bolyai University Cluj-Napoca, 2016)
This study proposes a critical analysis of the distribution of the rare plant species Amelanchier ovalis Medik. in the Romanian Carpathians. The species was mentioned as sporadically distributed in this part of Carpathians, but we found no evidence that the plant was ever collected and deposited in public herbaria. Besides herbarium material, a critical analysis of available botanical literature concurred to the same conclusion: the presence of Amelanchier ovalis in all previously mentioned localities in the Romanian Carpathians can not be supported by any concrete data and, therefore, can be considered as doubtful. The paper reports the recent discovery of Amelanchier ovalis in a new area in the Eastern Carpathians (Vrancea Mountains, Putna-Vrancea Natural Park). A detailed description of plant communities in which the species grows is also provided. Additionally, new sites with Hieracium telekianum Boros & Lengyel (Eastern Carpathian endemic and rare species) are also reported in Vrancea Mountains.
Keywords: Amelanchier ovalis; Chorology; Red Book; Romanian Carpathians; threatened species